1991
DOI: 10.1002/anie.199110321
|View full text |Cite
|
Sign up to set email alerts
|

Enediyne Compounds Equipped with Acid‐, Base‐ and Photo‐Sensitive Triggering Devices. Chemical Simulation of the Dynemicin A Reaction Cascade

Abstract: Fig. 3. Structure of the phenalenium ion o f 3 . CH,CI, (X = I) viewed perpendicular to the phenalenium plane with bond lengts [pm] and angles [' I (in brackets, standard deviations in units of the last decimal given) 1111.cation was found for the phenalenium moiety, and individual polymethine units could not be identified. Remarkable, however, is the high bond order, which can be deduced from the short C(2)-C(3), C(S)-C(6), and C(8)-C(9) distances (Fig. 3).113 (X = Br), which has the same structure as the iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…A similar route was followed also to prepare a second lactenediyne bearing at the β-lactam nitrogen a silyl removable group, in order to render such nitrogen atom able to be further elaborated. The overall yield of this synthesis, although longer than the previous one, was good, and it allowed us to prepare the final enediyne (27), as well as its silylated analogue, in a gram scale. Also in the case of lactenediynes with two additional handles a similar approach for the synthesis of the cyclic enediyne system was followed, 18 however this time the β-lactam (29) was assembled more convergently, by the use of a Staudinger condensation with (28), having a styryl ISSN 1424-6376…”
Section: β-Lactam-fused Enediynes: Lactenediynesmentioning
confidence: 90%
See 1 more Smart Citation
“…A similar route was followed also to prepare a second lactenediyne bearing at the β-lactam nitrogen a silyl removable group, in order to render such nitrogen atom able to be further elaborated. The overall yield of this synthesis, although longer than the previous one, was good, and it allowed us to prepare the final enediyne (27), as well as its silylated analogue, in a gram scale. Also in the case of lactenediynes with two additional handles a similar approach for the synthesis of the cyclic enediyne system was followed, 18 however this time the β-lactam (29) was assembled more convergently, by the use of a Staudinger condensation with (28), having a styryl ISSN 1424-6376…”
Section: β-Lactam-fused Enediynes: Lactenediynesmentioning
confidence: 90%
“…The final cyclization was carried on with the Nozaki reaction, so we converted in two high yielding steps the silyl enediyne into iodo enediyne (26). After oxidation of the alcohol, treatment with chromous chloride gave the desired products (27) in very good yields (Scheme 5). A similar route was followed also to prepare a second lactenediyne bearing at the β-lactam nitrogen a silyl removable group, in order to render such nitrogen atom able to be further elaborated.…”
Section: β-Lactam-fused Enediynes: Lactenediynesmentioning
confidence: 99%
“…The title compound was synthesized by literature methods (Leir, 1977;Kitamura et al, 2000). Quinoline derivatives have been shown to have anti-cancer and anti-malarial properties (Lee et al, 1991;Nicolaou et al, 1991). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Complexes containing the quinoline moiety can have pharmacological activity. Quinoline derivatives with additional substituents have good in anti-cancer and anti-malarial properties (Lee et al, 1991;Nicolaou et al, 1991) and this has aroused our inerest. Herein we describe the synthesis of the title compound and have determined its crystal structure.…”
Section: S1 Commentmentioning
confidence: 99%
“…Photo‐induced Bergman cyclization was uncovered in the 1990s by Sugiura,42 Nicolaou,43 and Wender 44. Later, Turro and Nicolaou revealed that simple artificial enediynes could also undergo cycloaromatization upon photo‐irradiation 45.…”
Section: Introductionmentioning
confidence: 99%